Eventual Role of Asymptomatic Cases of Dengue for the Introduction and Spread of Dengue Viruses in Non-Endemic Regions - Chastel, Claude (Frontiers in Physiology, 2012)
In dengue virus infections the asymptomatic cases are much more frequent than the symptomatic ones, but their true role in the introduction and subsequent spread of dengue viruses in non-endemic regions remains to de clarified. We analysed data from English and French literatures to assess if viraemia in asymptomatic dengue infections might be sufficient to represent a true risk. During outbreaks of dengue a large number of individuals are infected and since viraemia levels in symptomatic patients are known to vary by many orders of magnitude, it is reasonable to augur that a proportion of asymptomatic cases might reach levels of viraemia sufficient to infect competent mosquitoes. In addition, a number of new ways of contamination in man by dengue viruses were recently described such as blood transfusion, bone marrow transplantation and nosocomial infections that may be worth considering.